Pola Komunikasi Masyarakat Osing di Era Media - Serikit, Poundra Swasty Ratu Maharani (KOMUNITAS)
As one of traditional community in Indonesia, Lare Osing of Kemiren Village is capable of maintaining their local identity while welcoming the ever-improving modern technology and information. Their natural characteristic is indicated by their still-existing traditional social institutions which claim relatively high position in the community. However, the community somehow manages to open themselves towards a more modern and sophisticated form of institution. The objective of this writing is to describe the Communication Pattern of Osing Community of Kemiren Village of Glagah Subsdistrict of Banyuwangi Regency, East Java in the mass media age.